Dynaaminen vaikeustason säätö ja pelien käyttäjäkokemus: systemaattinen kirjallisuuskartoitus - Karhunen, Jaakko Pekka Oskari (2024)
The perceived difficulty level of video games has a great impact on the players' gaming experience. A game that is too easy or difficult can spoil the enjoyment of the game. The same game can be too easy for one player and too difficult for another at the same time, depending on the players' skills. Dynamic Difficulty Adjustment (DDA) aims to adjust the difficulty level during the game so that the difficulty level adapts to the player's skills. This thesis examines dynamic difficulty adjustment by carrying out a systematic literature review. The aim of the literature review is to find out what ways to implement DDA have been studied and how DDA has been found to affect the players' gaming experience. The most studied game genres are fighting, puzzle, platforming and shooting games. The DDA implementation methods used in the studied sources were divided into three categories, the most common of which is to modify the game's artificial intelligence. Based on the researched articles, DDA seems to help in making the difficulty of the games suitable for the players and makes the gaming experience more pleasant. The effect of DDA on the experience was not measured in a third of the articles. In four articles, disadvantages due to the use of DDA were also observed, which are also examined in the thesis.